Análise da qualidade em um restaurante regional: uma aplicação do modelo SERVQUAL - Silva, Ivana Priante da (Brasil, 2024)
The quality of service in restaurants plays a fundamental role in customer satisfaction and the success of the establishment. This perception of quality can vary from client to client, making it a challenge to meet all expectations. In this context, a study was conducted to analyze the quality of services offered by Peixaria Recanto do Quixito, a regional à la carte restaurant located in the municipality of Manaus. Using the SERVQUAL model as a methodology, the research evaluated the differences between customer expectations and their perceptions in relation to five dimensions of service quality, in order to verify the existence of gaps. Data were collected through questionnaires and analyzed quantitatively, revealing the need for improvements in some identified areas. The study contributes to the understanding of how service quality impacts the customer experience and the establishment's reputation, providing valuable insights to improve operations and meet growing consumer expectations in the competitive foodservice market. The results achieved were, in general, positive, with emphasis on the reliability and empathy dimensions, which presented all positive GAPs, which implies a level of customer satisfaction considered positive. Therefore, this research highlights the importance of companies exceeding the expectations and demands of their customers, in addition to being attentive to the excellence of the services provided.